2015
DOI: 10.1021/acs.langmuir.5b01171
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Growth of Metal Organic Framework/Graphite Oxide Composites through Pickering Emulsion and Their CO2 Capture Performance in the Presence of Humidity

Abstract: We proposed an in situ interfacial growth method induced by the Pickering emulsion strategy to produce metal organic framework (MOF)/graphite oxide (GO) composites of Cu3(BTC)2/GO, in which GO was demonstrated to be a promising stabilizer for producing the Pickering emulsion and provided a large interfacial area for the in situ growth of Cu3(BTC)2 nanoparticles. When Cu3(BTC)2/GO composites were used as adsorbents for CO2 capture from the simulated humid flue gas, they showed both significantly improved thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Bian et al proposed an in situ interfacial growth strategy for fabricating MOF/GO composites induced by the Pickering emulsion . In their study, GO was demonstrated to be a promising stabilizer for producing the Pickering emulsion and provide large interfacial area for the in situ growth of CuBTC nanoparticles.…”
Section: Co2 Capturementioning
confidence: 99%
“…Bian et al proposed an in situ interfacial growth strategy for fabricating MOF/GO composites induced by the Pickering emulsion . In their study, GO was demonstrated to be a promising stabilizer for producing the Pickering emulsion and provide large interfacial area for the in situ growth of CuBTC nanoparticles.…”
Section: Co2 Capturementioning
confidence: 99%
“…The H 2 O uptake of Cu 3 (BTC) 2 is 3.57 mmol g −1 and that of GO is 7.20 mmol g −1 , while those Cu 3 (BTC) 2 /GO‐n are 5.61, 7.15, and 5.96 mmol g −1 for n = 1, 2, and 3, respectively. All Cu 3 (BTC) 2 /GO samples show a greatly improved CO 2 uptake and CO 2 /H 2 O selectivity capacity under these conditions compared with the parent materials …”
Section: Gas Separation and Storagementioning
confidence: 98%
“…(3GO‐ZIF, 10GO‐ZIFand 15GO‐ZIF). a,g–i) Reproduced with permission . Copyright 2015, American Chemical Society.…”
Section: Gas Separation and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous work, 24,25 MOFs, with oil-soluble organic ligands and water-soluble metal ions [26][27][28] are especially suitable for the interfacial growth at the oil/water interface of emulsions. According to our previous work, 24,25 MOFs, with oil-soluble organic ligands and water-soluble metal ions [26][27][28] are especially suitable for the interfacial growth at the oil/water interface of emulsions.…”
Section: Introductionmentioning
confidence: 99%